Investigating the Prevalence and Impact Of Incivility In Medical Schools: A Review of the Literature - Wendy M Green; James M Durbin; Isis C Prior (Adult Education Research Conference, 2019)
Incivility in healthcare occurs at all levels, but is largely studied among nurses. The focus of this proposal is the prevalence and impact of incivility in graduate medical education.
Keywords: Incivility. Medical School.